NAC-MYB-based transcriptional regulation of secondary cell wall biosynthesis in land plants - Nakano, Yoshimi; Yamaguchi, Masatoshi; Endo, Hitoshi; Rejab, Nur Ardiyana; Ohtani, Misato (Frontiers in Plant Science, 2015)
Plant cells biosynthesize primary cell walls in all cells and produce secondary cell walls (SCWs) in specific cell types that conduct water and/or provide mechanical support, such as xylem vessels and fibers. The characteristic mechanical stiffness, chemical recalcitrance, and hydrophobic nature of SCWs result from the organization of SCW-specific biopolymers, i.e., highly ordered cellulose, hemicellulose, and lignin. Synthesis of these SCW-specific biopolymers requires SCW-specific enzymes that are regulated by SCW-specific transcription factors. In this review, we summarize our current knowledge of the transcriptional regulation of SCW formation in plant cells. Advances in research on SCW biosynthesis during the past decade have expanded our understanding of the transcriptional regulation of SCW formation, particularly the functions of the NAC and MYB transcription factors. Focusing on the NAC-MYB-based transcriptional network, we discuss the regulatory systems that evolved in land plants to modify the cell wall to serve as a key component of structures that conduct water and provide mechanical support.